ESTUDO DA EROSÃO SUPERFICIAL DO SOLO EM DIFERENTES FASES DE DESENVOLVIMENTO DA CULTURA DA BATATA NO MUNICIPIO DE IRATI-PR - Rogiski, Fabiana Laís (2021)
Potatoes are among the five most consumed foods in the world. Therefore, it is produced on a large global scale. Most of the potato planting is carried out in a conventional system, with intense traffic of agricultural equipment and soil tillage. However, systems that revolve the soil can cause changes in the soil structure, increasing erosion leading to soil degradation. The objective of this research was to evaluate how potato cultivation phases change the physical conditions of the soil and how these changes alter the erosive process. Data were collected on a farm in the municipality of Irati-PR with potato planting in a conventional system. The research was carried out during the 2020 harvest. The physical parameters evaluated were soil strength and aggregate stability, up to 60 cm deep and soil density up to 30 cm deep. Data were collected in the planting row and between the rows. The collections were carried out in the four phases of potato cultivation, being planting, heaping, tuber growth and senescence. After the rains and irrigations, water and soil were collected in 6 gutters. Each gutter had an area of 10m2. The results obtained showed that soil management in potato cultivation influences the water dynamics of the environment, alters soil physical characteristics such as soil resistance, density and stability of aggregates and, consequently, favors the production of sediments. The losses of water and soil found by this research show the need to seek alternatives to control erosion in potato growing areas under a conventional system. Among the alternatives, we can mention: contour-line planting, not planting (when possible) in areas with soil restrictions (shallow soils and steep slopes), deploying mechanical structures (small palisades) between the rows after heaping to reduce the formation of flow of water they generate from the concentration of water between thelines.